The Influence Of Interior Design And Service Quality On Consumer Satisfaction (Survey Of Coffee Shop Loger Consumer): - Abdussalam, Firman; Fitriadi, Budhi Wahyu; Arif (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
The Tasikmalaya City coffee industry is becoming more and more competitive due to the growing interest in the coffee shop sector. To get customers to the coffee shop, business players must provide the finest, particularly in a variety of areas. The purpose of this study is to ascertain how customer happiness at Loger Coffee is affected by interior design and level of service. This study has a quantitative design and employs questionnaires as a data gathering tool. One hundred participants were chosen for the study's sample using a straightforward purposive sampling method. The T Test and Coefficient of Determination are the methods utilized in the hypothesis testing phase of the study, whereas Multiple Regression analytical is the analytical methodology. The findings derived from this study include There are two partial effects on consumer satisfaction with Loger coffee: 1) Interior design has a 9.48% partial influence, and 2) Service quality has a 14.21% partial effect. 3) On customer satisfaction, interior design and service quality have a combined value of 7,422 and an R-Square value of 48,4% with regression equations Coffee Loger .